Zinnia Z. Wilson COVID-19 Photograph of Face Masks - Wilson, Zinnia Z.::::::::: (2022)
Photograph of Zinnia Z. Wilson's face masks sewn by Wilson's best friend's mother. The contributor writes, ". . . picture of 17 masks ordered for $112 by friend's Mom who has turned to sewing since she can't work. (She is 70)"